The Role of YouTube in Pronunciation Development: A Literature Review - Melgazo, Arnel; Cuevas, Edrian; Villagantol, Cleversel July; Aredidon , Maria Lovelyn; Minoza, Joemar (Journal of Language Development and Linguistics, 2025)
This literature review explores how YouTube helps students improve their speaking skills, especially their pronunciation. It looks at 20 studies published between 2020 and 2025 and compares YouTube-based learning to more traditional teaching methods. The review also covers how YouTube affects other speaking aspects like fluency and vocabulary, and what students and teachers think about using it. Most of the studies showed that YouTube is helpful because it gives real-life examples, native speaker input, and interactive features that keep learners interested. Still, there are some things that haven’t been studied enough—like whether the improvements last over time, how students use YouTube on their own, and how comfortable they are with using technology. In the end, the review suggests that YouTube can be a great tool for learning if it’s used with the right support and teaching approach.